Can someone please do a step by step proof for this or send me a link to a step by step webpage.(adsbygoogle = window.adsbygoogle || []).push({});

Thank you very much

Cosh^(-1 ) A/x=( x √(X^( 2 )+A ))/2a

my attempt=>

Cosh^(-1 ) = y

A/x = Cosh^(-1 )

A/x = Sechy

A/x= (2/(e^2 + e^-2))

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Proving Inverse Hyperbolic Function

**Physics Forums | Science Articles, Homework Help, Discussion**